Penyusunan Perencanaan Dan Pengendalian ProdukNPK PHONSKA Menggunakan Metode Time Series - Difanata; Rukmi, Hendang Setyo (e-Proceeding FTI, 2024)
PT. X is a company that plays an active role in supporting national agricultural activities by producing various kinds of fertilizer products. One of the products produced by PT. X is anonurea fertilizer. Production planning so far has been carried out based on top management's assessment and the results of the previous period's performance evaluation. The results of these plans often occur discrepancies with actual realization. Therefore it is necessary to do a production planning using other methods as a comparison in the production planning process. Based on the resources owned, namely in the form of historical data, the forecasting method that will be used as a comparison is the quantitative method with the time series method. The initial stage is the time series forecasting method which consists of moving averages, weighted moving averages, double exponential smoothing, linear regression with time. The second stage is the selection of the best method, namely the weighted moving average method. The third stage is data verification to determine the moving range, UCL, LCL, area A, area B. The results of the data verification are in the form of MR values. Based on data processing, the weighted moving average method is the best method that can be used as a comparison method with an error value of 11.11%. Keyword: Production Planning and Control, Time series Method, Forecasting PT. X merupakan perusahaan yang berperan aktif dalam mendukung kegiatan pertanian dengan cara memproduksi berbagai macam produk pupuk. Salah satu produk yang diproduksi oleh PT. X adalah pupuk non-urea. Perencanaan produksi selama ini dilakukan dengan berdasarkan penilaian top management serta hasil evaluasi performance periode sebelumnya. Hasil perencanaan tersebut kerap kali terjadi ketidaksesuai dengan realisasi aktual. Oleh karena itu perlu dilakukan suatu perencanaan produksi dengan menggunakan metode lain sebagai pembanding dalam proses perencanaan produksi. Berdasarkan sumber daya yang dimiliki yaitu berupa data historis maka metode peramalan yang akan digunakan sebagai pembanding adalah metode kuantitatif dengan metode time series. Tahap awal yang dilakukan metode peramalan time series yang terdiri dari moving average, weighted moving eaverage, double exponential smoothing, linear regression with time. Tahap kedua adalah pemilihan metode terbaik yaitu metode metode weighted moving average. Tahap ketiga verivifaksi data penentuan nilai moving range, UCL, LCL, daerah A, daerah B. Hasil verifikasi data tersebut berupa nilai MR. Berdasarkan pengolahan data yang dilakukan metode weightedmoving average merupakan metode terbaik yang bisa digunakan sebagai metode pembandingdengan nilai error sebesar 11,11%. Kata Kunci: Perencanaan dan Pengendalian Produksi, Metode Time series, Peramalan